Barrels XXX meeting report: Barrels in Baltimore. (2nd January 2018) - Shin, Hyeyoung; Bitzidou, Malamati; Palaguachi, Fernando; Brumberg, Joshua C.
Abstract: The Barrels meeting annually brings together researchers focused on the rodent whisker to cortical barrel system prior to the Society for Neuroscience meeting. The 2017 meeting focused on the classification of cortical interneurons, the role interneurons have in shaping brain dynamics, and finally on the circuitry underlying oral sensations. The meeting highlighted the latest advancements in this rapidly advancing field.